Including the patient voice in the development and implementation of patient‐reported outcomes in cancer clinical trials. (13th November 2019) - Addario, Bonnie; Geissler, Jan; Horn, Marcia K.; Krebs, Linda U.; Maskens, Deborah; Oliver, Kathy; Plate, Ananda; Schwartz, Erin; Willmarth, Nicole
Abstract: Context: Patient‐reported outcomes (PROs) are used in parallel with clinical evidence to inform decisions made by industry, clinicians, regulators, health technology assessment bodies and other health‐care decision‐makers. In addition, PRO data can also guide shared decision making and individual patient choice. Yet, the quality of many PROs in cancer clinical trials is suboptimal and requires improvement to add value to health care and policy decision making. Objective: To show how the integration of the patient and/or patient advocate at all stages of PRO development can help to realize the full potential of PROs. Methods: We examined the literature to show that the patient voice is often absent from the planning and implementation of PROs in cancer clinical trials. Good practice examples from the literature were combined with guideline recommendations, training or educational resources, and our own experience to create detailed practical steps for the inclusion of patients and/or patient advocates throughout PRO development. Results: Patient or patient advocates can play an active role in shaping PROs that are meaningful to the patient. They can contribute to content, choice of medium and implementation in a way that may support PRO completion and minimize missing data. Patients and their advocates can work to ensure PRO findings are disseminated appropriately in a way that is accessible to patients. Conclusion: This practical guidance aims to optimize PRO development and implementation in clinical trials, resulting in robust, relevant data that reflect the patient experience and that support decisions made by all stakeholders involved in research and health care.